Artificial Intelligence and Robotics in Surgery: The Future of Precision Medicine - ALHARBI, SAMI MOHAMMED; al harish, Tariq Mohammed; Attyah Zead Alqurashi, Eman; Alsubaie, Maha Dhuwihi; Alanazi , Njah Mohammad; Almutairi, Batool Alhamidi; Almotlaq , Hadeel Motlaq; KHABRANI, HUSSAIN ALI; Alsharari, Sayer Hamdan Salem; Alsharari, Tariq Maqbul Awadh; Alsharari, Yousef Dhaifallah Dabi (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Artificial intelligence (AI) and robotics signal a new domain for precision medicine and have fundamentally reformulated surgery into a new disciplinary lens that provides surgical practice with greater accuracy, efficiency, and outcomes. AI-powered systems, such as machine learning algorithms and computer vision, allow for real-time analysis of medical and surgical data, predictive modeling of patient outcomes, and personalization of treatment plans for each patient. In parallel, AI-powered robotic tools, such as the da Vinci Surgical System, offer surgeons a level of precision, control, and cognitive stimulation that rarely equates to manual techniques. This paper will outline the ongoing advancements, challenges, and potential opportunities that AI and robotics have in surgery. Also explored will be the implications for improved patient care relating to minimally invasive procedures, training for surgery, and patient safety. Significant applications of AI and robotics in surgery include autonomous surgical robots, image-guided robotic interventions, and advanced decision-support systems. Collectively, these clinical applications diminish opportunities for human mistakes and improve patient outcomes. However, the broad application of AI and robotics in surgery will depend on acting on ethical questions, regulatory legislation that is forward-thinking, and technical challenges, such as data and image quality, interoperability issues of robotic devices, and surgeon accountability. The challenges that impede the integration of AI and robotics in surgery can be addressed, but a successful practice application equates to future developments that produce the safest, most affordable, and individualized practice of surgery in the world. With the benefits of surgery supported by AI and robots being postulated, there remains a discipline-wide need for research, collaboration, and ethical accountability. This paper will therefore explore the advances of AI and robotics and conclude by emphasizing the importance of research on these approaches to shape the future of precision medicine.